2022
DOI: 10.1155/2022/9965334
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Administration of Volatile Oil from Citrus aurantium-Rhizoma Atractylodis Macrocephalae Alleviates Constipation in Rats by Altering Host Metabolome and Intestinal Microbiota Composition

Abstract: Background. The Citrus aurantium- (ZhiShi, ZS-) Rhizoma Atractylodis Macrocephalae (BaiZhu, BZ) pairs are often found in herbal formulas for constipation. The volatile oils of ZS and BZ (ZBVO) have good pharmacological activity against constipation, but the mechanism for treatment of slow transit constipation (STC) remains unclear. Method. A rat model using diphenoxylate tablets was constructed to investigate if transdermal administration of ZBVO would mediate intestinal microorganisms and fecal metabolites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Because intestinal peristalsis requires much energy, purines are among the most abundant metabolites in mammalian cells, and in addition to producing DNA and RNA molecules, purine nucleotides such as adenosine 5 phosphate and guanosine 5 phosphate are essential for providing cellular energy and intercellular signals, respectively. 50 Moreover, purine metabolites derived from the gut microbiota have been shown to relieve the impairment of the intestinal barrier function. Interestingly, enrichment of the purine pathway was observed in the AH group compared to the NR group.…”
Section: Resultsmentioning
confidence: 99%
“…Because intestinal peristalsis requires much energy, purines are among the most abundant metabolites in mammalian cells, and in addition to producing DNA and RNA molecules, purine nucleotides such as adenosine 5 phosphate and guanosine 5 phosphate are essential for providing cellular energy and intercellular signals, respectively. 50 Moreover, purine metabolites derived from the gut microbiota have been shown to relieve the impairment of the intestinal barrier function. Interestingly, enrichment of the purine pathway was observed in the AH group compared to the NR group.…”
Section: Resultsmentioning
confidence: 99%
“…With the deepening of modern pharmacological researches, increasing researches have demonstrated that A. lancea shows a certain effect in alleviating intestinal diseases. For example, it could reduce DSS-induced colitis by regulating intestinal flora and metabolites [ 29 ], as well as relieving constipation by regulating intestinal flora [ 30 ]. It is clear that intestinal flora plays a crucial role in resulting in GI diseases.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 had a reparative effect on dextran sulfate sodium (DSS)-induced intestinal damage by upregulating IL-6 and colony stimulating factor 3 (CSF3) ( Shi et al, 2019a ; Shi et al, 2019b ). Alterations in intestinal microbiota were involved in the regulation of inflammatory factor expression, with Ruminococcaceae negatively correlated with IL-6 and TNF-α ( Wang et al, 2022 ). Besides, overexpression of TLR4 also resulted in an increased abundance of SCFA-producing bacteria, like Bacteroidetes, a class of gut beneficial microbes thought to enhance immune function and protect intestinal health.…”
Section: Discussionmentioning
confidence: 99%